New directions for the realisation of SDGs given the economic and welfare costs incurred by air pollution - Jasińska-Biliczak, Anna; Ikwuwunna, Eugene (Frontiers in Environmental Science, 2023)
Air pollution is a multidisciplinary research field, which affects sustainable development (SD) and Sustainable Development Goals (SDGs). Its multi-level cause and effect shows the direct influence of air pollution on human health, standards and costs of living, health treatment, and the economies of states. Poor air quality, as an SDG factor, may affect both lower wellbeing and economic growth. As developed economies have faced problems due to poor air quality, they have worked out solutions based on their technological engagement. However, emerging economies are still facing poor air quality as a main problem affecting their economic growth. The particulate matter factor, according to the air quality study, was used as the basis for comparative and statistical research. The findings of the study indicate that air pollution causes a serious impact relating to workforce productivity, absence from work, mortality, and even lower crop yields. There is an obvious research gap in the investigated field of comparative studies considering air pollution as an SD factor, understood as an economic concept. Therefore, the current study is proposed to fulfil this gap, contribute to the knowledge base of the factors affecting human development, and expand the statistical data based on the findings from a comparison between Poland and Germany on their performance in air quality tests. This is a novel approach pointing to air pollution as the proposed focus of research for the realisation of SDGs.